(untitled) (Research, Society and Development, 2022)
Over the last century, social evolution in relation to human rights, together with the claims of the feminist movement, has conquered numerous rights for women, among them, the right to exercise different professions and even to manage their own business. Therefore, this article aims to understand what are the challenges that women entrepreneurs have to face in order to manage their businesses. This is a qualitative and exploratory literature review, with a search in the digital collections of scientific publications SciELO (Scientific Electronic Library Online), BTDT (Brazilian Digital Library of Theses and Dissertations) and Google Scholar. From the reading of the selected texts, it was possible to understand that there are many challenges that women have to face in order to be able to successfully undertake, being possible to mention: the need to reconcile the management of the business with family responsibilities; lack of confidence in its capabilities by suppliers and customers; little support from family and friends; greater difficulty in obtaining lines of credit. In this sense, it was concluded that there is a great discrepancy in the difficulties faced by women entrepreneurs in relation to men, requiring greater resilience to face them and achieve the desired success.